Pelanggaran Ruang Udara oleh Pesawat Asing Menurut Hukum Internasional dan Hukum Nasional Indonesia - Sefriani Sefriani (Fakultas Hukum Universitas Islam Indonesia, 2015)
A country has an absolute and exclusive sovereignty for its airspace. Sovereign country has right to manage flight routes and its airspace, regarding the fact that airspace is very strategic for its defense and security. Violations of Indonesia’s airspace sovereignty by either civilian aircraft or state aircraft often occur. The problem discussed is: how are the legal arrangement and law enforcement related to the violations of a country’s sovereign territory according to international law and Indonesia’s national law. The research method was normative legal research with statute approach, historical approach, conceptual approach, and comparative approach. The research finding was presented in the form of descriptive analysis. The result concludes that neither international nor national law is strict enough in determining the legal status parameter of an aircraft, whether it is civilian or state aircraft. Such thing can result in a serious conflict related to the regulations for such aircraft.